Neuroprotective effects of Withania somnifera in BPA induced-cognitive dysfunction and oxidative stress in mice - Birla, Hareram; Keswani, Chetan; Rai, Sachchida Nand; Singh, Saumitra Sen; Zahra, Walia; Dilnashin, Hagera; Rathore, Aaina Singh; Singh, Surya Pratap (Behavioral and brain functions, 2019)
Background Bisphenol A (BPA), a major endocrine disruptor and a xenobiotic compound is used abundantly in the production of polycarbonate plastics and epoxy resins. Human exposure to this compound is primarily via its leaching from the protective internal epoxy resin coatings of containers into the food and beverages. In addition, the plastics used in dental prostheses and sealants also contain considerable amount of BPA and have a high risk of human exposure. Since it is a well-known endocrine disruptor and closely mimics the molecular structure of human estrogen thereby impairing learning and memory. Withania somnifera (Ws), commonly known as Ashwagandha is known for its varied therapeutic uses in Ayurvedic system of medicine. The present study was undertaken to demonstrate the impairment induced by BPA on the spatial learning, working memory and its alleviation by Ws in Swiss albino mice. The study was conducted on thirty Swiss albino mice, randomly distributed among three groups: control, BPA and BPA + Ws. The behavioral recovery after treatment with Ws was investigated using the Y-maize and Morris water maize test. Whereas, for the estimation of recovery of NMDA receptor which is related to learning and memory in hippocampus region by western blot and immunohistochemistry. Furthermore, the oxidative stress and antioxidant level was assessed by biochemical tests like MDA, SOD and catalase. Results The study revealed that administration of Ws alleviated the behavioral deficits induced by BPA. Alongside, Ws treatment reinstated the number of NMDA receptors in hippocampus region and showed anti-oxidative property while ameliorating the endogenous anti-oxidant level in the brain. Conclusion These findings suggest that Ws significantly ameliorates the level of BPA intoxicated oxidative stress thereby potentially treating cognitive dysfunction which acts as the primary symptom in a number of neurodegenerative diseases.